Preliminary design of human powered submarine [compact disc] - 209826 Lee, Khian Whatt (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2006